2012
DOI: 10.2174/138161212801327284
|View full text |Cite
|
Sign up to set email alerts
|

A Physico-Biochemical Study on Potential Redox-Cyclers as Antimalarial and Antischistosomal Drugs

Abstract: The role of redox enzymes in establishing a microenvironment for parasite development is well characterized. Mimicking human glucose-6-phosphate dehydrogenase and glutathione reductase (GR) deficiencies by redox-cycling compounds thus represents a challenge to the design of new preclinical antiparasitic drug candidates. Schistosomes and malarial parasites feed on hemoglobin. Heme, the toxic prosthetic group of the protein, is not digested and represents a challenge to the redox metabolism of the parasites. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 88 publications
2
24
0
Order By: Relevance
“…It is likely that P. berghei can uptake GSH from the host, as opposed to P. falciparum [151]. However, of greater importance is the NADPH flux, which can be diverted to a futile cycle in the presence of redox-active agents by exploiting the GR reductive catalysis for drug bioactivation in infected red blood cells and/or drug combination in concert with metHb catabolism [22, 29, 43, 156]. …”
Section: The Impact Of Glutathione Reductase Inhibition On the Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that P. berghei can uptake GSH from the host, as opposed to P. falciparum [151]. However, of greater importance is the NADPH flux, which can be diverted to a futile cycle in the presence of redox-active agents by exploiting the GR reductive catalysis for drug bioactivation in infected red blood cells and/or drug combination in concert with metHb catabolism [22, 29, 43, 156]. …”
Section: The Impact Of Glutathione Reductase Inhibition On the Growthmentioning
confidence: 99%
“…(1)). The molecular mechanisms by which inhibition of hemozoin formation occurs has been recently detailed and reviewed for different series of antimalarial drugs, including methylene blue [22], 1,4-naphthoquinones and xanthones [29]. In order to correlate the contribution of the redox-cycling capabilities of these molecules to the antiplasmodial activity, three key-assays were set up to allow probing and differentiating the mechanisms of drug actions with relevant heme species under quasi-physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, methylene blue and certain 1,4-naphthoquinones accept electrons from the flavoprotein glutathione reductase (GR), which is itself reduced by NADPH (22,25). After reduction, these compounds can transfer single electrons to key oxidants of P. falciparum, e.g., to the hemoglobin catabolites methemoglobin and Fe(III)-protoporphyrin IX (22,24,26). The generated Fe(II) species are toxic to the parasite since Fe(II)-containing oxyhemoglobin is a poor substrate of the hemoglobinase falcipain-2 (27), and Fe(II)-protoporphyrin IX was shown to inhibit the crystallization of ␤-hematin in vitro (28).…”
mentioning
confidence: 99%
“…Methylene blue, which is still the drug of choice in the treatment of methemoglobinemia, has recently regained interest for its antiplasmodial activities (66)(67)(68), especially as a companion drug in combination therapies (69,70) or as a potential transmission-blocking agent (17). Similar to benzylmenadiones, methylene blue seems to exert its antiplasmodial activity by causing a redox imbalance (9,71). However, the blue dye colors the body fluids, such as the urine, and the eyes of the patients, which is a limiting factor for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the mode of action have suggested that plasmodione, like other benzylmenadione derivatives, acts as a redox cycler, thereby disrupting the redox homeostasis of the parasitized erythrocyte (3,(8)(9)(10)(11). Interfering with the parasite's redox balance is a largely unexploited but highly effective strategy to restrict parasite development.…”
mentioning
confidence: 99%